Effect of temperature on task performance and thermal comfort among undergraduates of UMP - Tan, Zhen Sheng (2016)
Indoor air temperature may negatively affect human performance rate and human physical response if it is not properly controlled. Effects of indoor air temperature on task performance and its contribution to the occurrence of thermal comfort had become a focus of studies. However, until now inconsistent results were yielded from those studies. In this paper, the relationship between the thermal comfort and task performance was discussed, as well as the thermal comfort among respondents. Typing test was used as an indicator of evaluating task performance. ASHRAE Thermal Sensation Scale was also used to evaluate the range of acceptance temperature. Based on the result, 23°C is the most comfortable temperature and most accepted. In conclusion, the study showed that thermal comfort (p<0.05) and task performance (p<0.05) were significantly difference under different temperature settings, but thermal comfort did not show any relationship with task performance (p>0.01).